Time Interval From Early-Term Antenatal Corticosteroids Administration to Delivery and the Impact on Neonatal Outcomes - Li, Jing; Zhang, Jing; Hao, Qingfei; Du, Yanna; Lu, Jie; Chen, Haoming; Cheng, Xiuyong (Frontiers in Pediatrics, 2022)
Abstract Objectives: To determine the association between the time interval from antenatal corticosteroids administration to delivery and neonatal complications in diabetic mothers undergoing early term (37+0 to 38+6 weeks) scheduled cesarean section (ETSCS). Study design: A retrospective cohort study of women with gestational diabetes mellitus (GDM) in pregnancy undergoing ETSCS were included. Cases were stratified into the following groups based on the time interval from the first dose of corticosteroids administration to delivery: <2 days, 2 to 7 days, and >7 days. Women undergoing ETSCS who did not receive corticosteroids were included as controls. We assessed the association between the time interval and neonatal outcomes in a multivariate regression model that controlled for potential confounders. Primary outcomes were incidence of respiratory distress syndrome (RDS)/transient tachypnea of the newborn (TTN) and neonatal hypoglycemia. Results: The study cohort comprised 619 neonates. Of those, 70 (11.3%) delivered within 2 days of maternal corticosteroids administration, 98 (15.8%) delivered within 2 to 7 days after maternal corticosteroids administration, and 77 (12.4%) delivered more than 7 days after maternal corticosteroids administration. The remaining 374 (60.4%) were not exposed to corticosteroids. Multivariate analysis demonstrated that delivery within any time of antenatal corticosteroids administration was not associated with increased risks of RDS/TTN. The incidence of neonatal hypoglycemia tended to be greater in infants exposed to antenatal corticosteroids, especially those born within 2 days after corticosteroids administration (<2 days: aOR 4.507, 95% CI 0.648-31.336; 2 to 7 days: aOR 1.412, 95% CI 0.287-6.958; >7 days: aOR 1.446, 95% CI 0.206-10.125). Conclusions: Corticosteroids treatment for diabetic mothers undergoing ETSCS was not associated with neonatal respiratory outcomes, but was found predisposing to increase the risk of neonatal hypoglycemia, especially when delivery occurred ＜2 days after antenatal corticosteroids treatment.